Fundamental Properties of Magnesium Phosphate Cement Mortar for Rapid Repair of Concrete - Joon Woo Park; Ki Hwan Kim; Ki Yong Ann (Advances in Materials Science and Engineering)
Fundamental properties of magnesium phosphate cement (MPC) were investigated in this paper. The setting time and compressive and bond (i.e., flexural and tensile bond) strengths were measured to assess the applicability, and hydration product was detected by the X-ray diffraction. The specimens were manufactured with magnesia and potassium dihydrogen phosphate (K2HPO4) was added to activate hydration process. The Borax (Na2B4O7·10H2O) was used as a retarder to mitigate overwhelming rapid hardening. Mercury intrusion porosimetry was used to examine the pore structure of MPC mortar, and simultaneously rapid chloride penetration test was performed. As a result, the compressive strength of MPC mortar was mostly achieved within 12 hours; in particular, the MPC mortar at 4.0 of M/P ranked the highest value accounting for 30.0 MPa. When it comes to tensile and flexural bond to old substrate in mortar patching, the MPS had the higher tensile and flexural strengths, accounting for 1.9 and 1.7 MPa, respectively, compared to OPC mortar patching. Unlike Portland cement mortar, the MPC mortar contained mainly air void rather than capillary pores in the pore distribution. Presumably due to reduced capillary pore in the MPC, the MPC indicated lower penetrability in the chloride penetration test.